Perilaku Pemberantasan Sarang Nyamuk pada Masyarakat Desa Karangjati Kabupaten Blora - Erni Nuryanti; Syamsulhuda Budi Mustofa; Kusyogo Cahyo (Jurnal Promosi Kesehatan Indonesia, 2011)
Based on the data during 2006-2009, there were always dengue hemorrhage fever patients in Karangjati village, Blora regency. The objective of the research is to know some factors which influence the acts to exterminate moquito nest among people in Karangjati village Blora regency. This is explanatory research of which research method is survey which uses cross sectional approach. There are respondents who were chosen randomly. The data was taken by using questionnaire and then it was analyzed using univariate, bivariate and multivariate. Variables which relates to behaviour toward mosquito nest extermination are knowledge, attitude, information availability, and health official role. Variables which relates to behaviour toward mosquito nest extermination are age, education, sex, income.